1986
DOI: 10.3109/02713688609020052
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-potassium-dependent-ATPase activity in Emory mouse lens

Abstract: Previous morphological and biochemical studies indicate that a late appearing hereditary Emory mouse cataract may be a good model for certain human senile cataracts. The development of lenticular opacity in the Emory mouse is a slow process which provides an opportunity to conduct analysis of the progression of alterations that lead to cataract development. Biochemical investigations have not yet demonstrated any specific correlation between alterations in the lens and the extent of opacity. We have conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The mechanisms for this reduction in Na ϩ ,K ϩ -ATPase activity are not completely understood but could result from an endogenous inhibitor or reductions in functional sodium pump units. We have recently isolated a labile, endogenous Na ϩ ,K ϩ -ATPase inhibitor from the peritoneal dialysate of hypertensive renal failure patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] The mechanisms for this reduction in Na ϩ ,K ϩ -ATPase activity are not completely understood but could result from an endogenous inhibitor or reductions in functional sodium pump units. We have recently isolated a labile, endogenous Na ϩ ,K ϩ -ATPase inhibitor from the peritoneal dialysate of hypertensive renal failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Rodriguez-Sargent et al 2 recently reported that development of cataracts in Dahl S rats in response to a high salt diet can be predicted by a reduction in ouabain-sensitive Na ϩ ,K ϩ -ATPase activity several weeks before cataract formation. Likewise, a reduction in lens Na ϩ ,K ϩ -ATPase (sodium pump) activity occurs in several other animal models of cataract [2][3][4][5] and in human cataract formation. 3,6 -8 A similar reduction in sodium pump activity is also a common feature of hypertension and is thought to be mediated in part by a circulating sodium pump inhibitor 9 called either digitalis-like factor (DLF) or ouabain-like factor.…”
mentioning
confidence: 99%
“…The Emory mutants develop late-onset light opacity around 7 months old and progressively turn into dense cataracts later at older age [Kuck et al, 1981; Kuck, 1990]. A number of biochemical and morphological studies have reported that many different changes are associated with the cataract formation [Kuck et al, 1981; Bhuyan et al, 1982; Swanson et al, 1985; Rathbun et al, 1986; Unakar et al, 1986; Lo and Kuck, 1987; DeNagel et al, 1988; Takemoto et al, 1988; Kuck and Kuck, 1989; Shi and Bekhor, 1992; Taylor et al, 1995; Reddy et al, 1999; Congdon et al, 2000; Sheets et al, 2002]. …”
Section: Introductionmentioning
confidence: 99%